ANALISISKELAYAKAN AGUNAN TAMBAHAN PEMBIAYAAN MURABAHAH KHUSUS PEGAWAI (STUDI KASUS PT BPRS GAJAH TONGGA KOTO PILIANG, KECAMATAN SILUNGKANG) - Hasnir Rahmi Febria; Amsah Hendri Doni (CV. Adiba Aisha Amira, 2024)
The primary focus of this research is the idea of extra collateral evaluation of PT BPRS Gajah Tongga Koto Piliang's murabahah financing. Islamic banks must have a strong collateral evaluation procedure in place before offering loans in order to reduce the possibility of bad financing. In actuality, however, the field's facts contradict the current idea. The objective of this research is to ascertain the extra collateral evaluation procedure that PT BPRS Gajah Tongga Koto Piliang employs for special employee murabahah financing. Additionally, to assess the appeal of PT BPRS Gajah Tongga Koto Piliang's murabahah financing to clients who are special employees. This research uses a qualitative descriptive technique utilizing data from interviews. Data was gathered via interviews with special employee murabahah financing clients and employees of PT BPRS Gajah Tongga Koto Piliang. The study's findings suggest that PT BPRS Gajah Tongga Koto Piliang has not been successful in determining whether or not further collateral would be necessary for special employee murabahah financing. Second, the fact that PT BPRS Gajah Tongga Koto Piliang offers financing to special employee clients at an attractive margin of just 12% is what draws them in.